SPIRITUALITAS BERJUANG MENJADI MISKIN DAN BERJUANG BAGI KAUM MISKIN - Salmon Pamantung (Al-Qalam, 2012)
Poverty and injustice are the face of Mammon that church has to against for. Both are shown in economicsstructure, social matter and religios legitimation that tear and scattering the humanity: Jesus ministrywas against to mammon, include to the poverty and injustiice. By struggling to become impecunious andstruggle for pauper, Jesus unload the poverty and injustice, pass the crucify event in Kalvari. Church asbelievers community and followers of Jesus have to inspire the spirituality of Jesus in theology andpraxis through advocating and stand up for the oppressed and impecunious people. The " struggling tobecome impecunious and struggle for pauper Sprituality, Jesus unload the poverty and the injustice,pass the event crucify in Calvari. Church as community believe and follower of Jesus have tomenginiernalisasi spirituality of Jesus in theology and praxis advocating to feel and stand up for theoppressed and impecunious people.